Brief Communication: Twelve-year cyclic surging episodes at Donjek Glacier in Yukon, Canada - T. Abe; M. Furuya; D. Sakakibara (The Cryosphere, 2016)
Surge-type glaciers repeat their short active phase and their much longer quiescent phase usually every several decades or longer, but detailed observations of the evolution cycles have been limited to only a few glaciers. Here we report three surging episodes in 1989, 2001, and 2013 at Donjek Glacier in the Yukon, Canada, indicating remarkably regular and short repeat cycles of 12 years. The surging area is limited within the ∼ 20 km section from the terminus, originating in an area where the flow width significantly narrows downstream, suggesting a strong control of the valley constriction on the surge dynamics.